A study on correlation between allergen and allergic contact dermatitis - Nagure, Ashok Kumar B.; Kalyanrao Y., Guruprasad (International Journal of Research in Dermatology, 2017)
Background: Agents which cause contact dermatitis are simple chemical compounds and by themselves these agents will not cause sensitization and are called haptens. These require another molecule usually a protein called the carrier molecule derived from the epidermis to cause allergic sensitization. The confirmation of contact dermatitis is done by the patch testing. There is no substitute for the patch test in the management of allergic contact dermatitis. Methods: After selecting the patient suspected to have allergic contact dermatitis the findings were recorded in the proforma which also includes the systemic examination of CVS, CNS, GIT and respiratory system to study systemic correlation if any. Investigation were done which included Hb%, TLC, DLC, urine routine and microscopic examination, patch testing and other special investigations if required. The patient was subjected to patch testing after the acute stage has subsided and the patient was on no therapy with topical or systemic steroids prior to patch testing. Results: The incidence of allergic contact dermatitis due to cosmetics was found in 7 (5.6%) cases. In that hair dye (PPD) inducing dermatitis was found in 4 (57.4%) and due to hair oil 1 (14.2%), kumkum 1 (14.2%) and Sunsilk shampoo 1 (14.2%). The incidence of PPD sensitivity in this series of 125 cases was 4 (3.2%). Conclusions: PPD is a well-known potent sensitizer, it is a chief constituent of the commonly used hair dyes and also some other cosmetics like nail polish.